Absolute Batman. Vol. 1, The zoo - Snyder, Scott (DC Comics, 2025)
"Without the wealth, without the cave, he's still the Absolute Dark Knight! Meet Batman as you've never seen him before, reimagined with a modern origin story at the hands of superstar creative team Scott Snyder and Nick Dragotta! An astonishing new version of DC's iconic characters is here! In the Absolute Universe, familiar heroes have been reinvented from the ground up with origin stories that completely reshape both their abilities and their circumstances but maintain the core characteristics that fans have known and loved for decades! Bruce Wayne comes from nothing. He's not the scion of a wealthy empire in Gotham City, he's the son of a public school teacher who he experienced the unimaginable horror of random gun violence as a child, changing the trajectory of his life forever. With no limitless resources, no billions to fund him, no mansion, and no butler to care for him, Bruce has shaped himself into an entirely different breed of Batman, one that is equal parts brain and brawn, who exists exclusively in the grittiest and most underserved parts of Gotham with no high society mask to fall back on."--Amazon.com.